The first high-resolution meteorological forcing dataset for land process studies over China - He, Jie; Yang, Kun; Tang, Wenjun; Lu, Hui; Qin, Jun; Chen, Yingying; Li, Xin (Scientific data, 2020)
The China Meteorological Forcing Dataset (CMFD) is the first high spatial-temporal resolution gridded near-surface meteorological dataset developed specifically for studies of land surface processes in China. The dataset was made through fusion of remote sensing products, reanalysis datasets and in-situ station data. Its record begins in January 1979 and is ongoing (currently up to December 2018) with a temporal resolution of three hours and a spatial resolution of 0.1°. Seven near-surface meteorological elements are provided in the CMFD, including 2-meter air temperature, surface pressure, and specific humidity, 10-meter wind speed, downward shortwave radiation, downward longwave radiation and precipitation rate. Validations against observations measured at independent stations show that the CMFD is of superior quality than the GLDAS (Global Land Data Assimilation System); this is because a larger number of stations are used to generate the CMFD than are utilised in the GLDAS. Due to its continuous temporal coverage and consistent quality, the CMFD is one of the most widely-used climate datasets for China. Measurement(s) temperature • pressure • humidity • atmospheric wind speed • radiation • precipitation process Technology Type(s) digital curation Factor Type(s) geographic location • time Sample Characteristic - Environment climate system Sample Characteristic - Location China Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.11558439